Orbital-selective Dirac fermions and extremely flat bands in frustrated kagome-lattice metal CoSn - Zhonghao Liu (Nature Portfolio, 2020)
The understanding of kagome bands, which are characterized by Dirac-like bands capped by a flat band, remains largely elusive. Here, Liu et al. report the observation of a flat band and Dirac bands as ideal features of kagome bands in CoSn, revealing orbital-selective character.